TypeScript essentials develop large scale responsive web applications with TypeScript - Nance, Christopher (Birmingham [England] : Packt Publishing, 2014)
Annotation The book introduces the TypeScript language and its features to anyone looking to develop rich web applications. Whether you are new to web development or are an experienced engineer with strong JavaScript skills, this book will get you writing code quickly. A basic understanding of JavaScript and its language features are necessary for this book.
Description based on print version record.
Keywords: COMPUTERS / Software Development & Engineering / Tools; COMPUTERS / Software Development & Engineering / General; TypeScript (Computer program language); Electronic books